Reducing Child Support Debt and Its Consequences: Can Forgiveness Benefit All? - Heinrich, Carolyn J.; Burkhardt, Brett C.; Shager, Hilary M. (My University, 2010)
This evaluation of a demonstration program that targeted noncustodial parents with high levels of unpaid child support debt and offered them incentives to become regular payers finds that participants paid more toward their child support obligations, made more frequent payments and reduced their debt balances.